Islam di Inggris (Tinjauan Historis Dinamika Kehidupan Muslim) - Mundzir, Chaerul (Rihlah: Jurnal Sejarah dan Kebudayaan, 2015)
The aim of this essay is to describe about the Dynamics of Muslim’s life in England within historical perspective. In general perspective, England is an area which is Muslim population no longer. Since 1860 Islam have entered in that area, additionally, based on the England Population Statistics, England is an area in western civilization whose massive Muslim peoples. It was caused by a multiculturalism policy made of England Government in 1961. The policy that is used to sustain the human resources for each immigrant has been changing for Muslims in England territory. Futhermore, Muslims can perform the Islamic regulation (sharia) among the non-Muslim people in the society. However, Muslim in England has to face the presence some of islamophobic organizations such as English Defence League (EDL), Afro-Carribean and others which always disturb Muslims life in England.